Peran Hukum terhadap Tindak Pidana Pemberitaan Palsu oleh Jurnalis Berdasarkan Undang-Undang Nomor 40 Tahun 1999 - Sonya Airini Batubara; Timotius Reynata Sinuraya; Teresia Oktaviani Napitupulu; Rizal Maruli Lambok Sitorus (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
The proliferation of hoaxes in the era of information transparency, committed not only by the public but also by journalists, forms the background of this research. This phenomenon raises legal concerns because journalists are required to provide accurate, balanced, and responsible information in accordance with Law Number 40 of 1999 concerning the Press. This study aims to examine the legal implications for journalists who engage in false reporting and to analyze how the law regulates the dissemination of false news by journalists. The research employs a normative juridical method using statutory, conceptual, and case approaches. Data were obtained from primary, secondary, and tertiary legal materials and analyzed qualitatively using a deductive approach. The findings reveal that Law Number 40 of 1999 does not specifically regulate criminal sanctions for false reporting by journalists, but instead prioritizes settlement through the Press Council and the Journalistic Code of Ethics, including the right of reply and correction. Nevertheless, journalists may still face legal responsibility under the Indonesian Criminal Code and the Electronic Information and Transactions Law if false reporting fulfills criminal elements. Therefore, law functions both as a protector of press freedom and as a limitation to prevent abuse, with ethical, administrative, and criminal sanctions applicable to journalists and press institutions.